APLIKASI PENJUALAN ALAT TULIS KANTOR (ATK) PADA TOKO 1001 - Alam, Syahirun; Hamra, Hamra; Lina, Herlina (Fakultas Teknik Universitas Muhammadiyah Parepare, 2021)
An application is needed in every business organization, which functions as a supporter of business services. For example, in the area of ​​sales business organizations, applications are needed to manage supplier data, goods and transactions. Toko 1001 is one of the office stationery sales business organizations that requires applications as a service support where every month Sinar Agung Stores buy goods that will later be used as stock sales of goods to then be sold to customers.This office stationery sales application was built using the Pascal programming language with the web (PHP) programming application. While the database used is the PHP database.The testing done in testing this application is to use the Black Box test which states that the system is running as needed and free from errors.